Chapter 0 - Proofs





Terminology



Hints for Finding Proofs



Types of Proof: Proof by Construction



Types of Proof: Proof by Contradiction



Types of Proof: Proof by Induction



Proof by Induction: Example

Let $P(n)$ be the statement $\displaystyle \sum_{i=1}^n i = \frac{n(n+1)}{2}$.

Prove P(n)n ≥ 1. Use proof by induction. Prove $P(n) \forall n \ge 1$. Use proof by induction.

  1. Basis: Prove $P(1)$, that is, that $\displaystyle \sum_{i=1}^1 i = \frac{1(1+1)}{2}$. But $\displaystyle \sum_{i=1}^1 i = 1$ and $\frac{1(1+1)}{2} = 1$, and this proves $P(1)$.
  2. Inductive Step: Assume $P(k)$ for an arbitrary k ≥ 1. This is the Inductive Hypothesis. Now we must show that $P(k)$ implies $P(k+1)$, that is, that $\displaystyle \sum_{i=1}^{k} i = \frac{(k)(k+1)}{2}$ implies that $\displaystyle \sum_{i=1}^{k+1} i = \frac{(k+1)(k+1+1)}{2}$. (In other words, P(k) P(k+1)).

    $ \displaystyle \begin{align*} \text{Now } \sum_{i=1}^{k+1} i & = \sum_{i=1}^{k} i + (k+1), \text{by definition of summation} \\ & = \frac{k(k+1)}{2} + (k+1), \text{by the Inductive Hypothesis} \\ & = \frac{k^2+k+2k+2}{2} \\ & = \frac{k^2+3k+1}{2} \\ & = \frac{(k+1)(k+2)}{2} \\ & = \frac{(k+1)(k+1+1)}{2} \end{align*} $

  3. Thus, we have proved that $\displaystyle \sum_{i=1}^{k+1} i = \frac{(k+1)(k+1+1)}{2}$, which is $P(k+1)$. Thus, from $P(k)$ we have proved $P(k+1)$.

  4. Therefore, from 1 and 2 we conclude by induction that P(n) is true for all n ≥ 1















ITEC 420 Course Page